PENGARUH AUDIT TENURE, UKURAN AUDITOR, SPESIALISASI AUDIT DAN AUDIT CAPACITY STRESS TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang listed di BEI tahun 2010-2015) - Deddy Kurniawansyah (Universitas Airlangga, 2016)
The purpose for this research is to test audit tenure, auditor size, audit specialization industry, and audit capacity stress to earning management manufacture industry listed in the BEI in 2010-2015. In this research, we use leverage, firms size, and ROA as Control variable. This study population was manufacture industry listed in the BEI in 2010-2015. This population use criteria population by 703 annual reports manufacture industy. The sampling used in this study a sensus method. Source of data is secondary data, obtained from annual reports of manufacture industry in BEI. This study used multiple regretion analysis to analysis data with the help of the program Partial Last Square (PLS). The results obtained in this study is audit tenure, and audit capacity stress has a positive effect on earning management manufacture industry. Auditor size, and audit specialization industry has a negative effect on earning management manufacture industry. For control variable, the results obtained is leverage, firms size, and ROA has a positive effect on earning management manufacture industry. The results provide more informed basis for investors to be more selective in investing their funds. To reduce earnings management practices in companies should principals switched auditors periodically or less than 3 years, and using scale big four auditors, and has specialized audit industry. Keyword : audit tenure, auditor size, audit specialization industry, audit capacity stress, earnins management